(untitled) (diségno, 2018)
In recent years construction industry is crossing an innovation process based on the digitization of information to reliably describe the existing architectural heritage. Therefore, the need to adopt a new graphic language based on information modelling that summarises graphic and alphanumeric characteristics of a certain building has emerged. This contribution focuses on the analysis of aspects that have characterized the idea of representation in the past, proposing information modeling as a natural renewal of design representation through digital technologies.